SRI METHOD - A WATER SAVING TECHNOLOGY IN RICE - PRESENT STATUS AND FUTURE PROSPECTS - T. VIDHAN SINGH, B. NIRMALA, P.C. LATHA,, R. MAHENDER KUMAR, K. SUREKHA, B. SREEDEVI, CH. PADMAVATHI, D. SRINIVAS (The Journal of Research, PJTSAU, 2019)
The water demand in the year 2000 was 634 km3 and it is likely to be 1,093 km3 by the year 2025. Due to rapid rise in population and growing economy of the country, there will be continuous increase in demand for water, and it will become scarce in the coming decades. While India is considered rich in terms of annual rainfall and total water resources, its uneven geographical distribution causes severe regional and temporal shortages. However, there exist considerable spatial area temporal variation in the distribution of rainfall and hence unavailability of water. There are technologies for reducing water requirement of rice in India. Among them, System of Rice Intensification (SRI)1 , an alternate rice cultivation methodology developed in Madagascar 25 years ago is gaining wider acceptance in many countries including India. SRI method claims to greatly enhance water productivity and grain yield but there is lack of understanding of scientific principles underlying and synergetic effects of the principles followed in SRI method especially in Indian conditions. Hence, in the present paper, significance and necessity of SRI and summarises the results of the evaluation of SRI method across the country at 25 locations for four years and the results obtained regarding various practices of SRI at Directorate of Rice Research(DRR). The results clearly indicated 7-20 per cent higher grain yield over the traditional irrigated transplanted rice across the country in different soil and climatic situations. SRI method resulted in higher nutrient use efficiency without depleting the soil available nutrients as compared to conventional transplanting after two seasons of the study. The varieties having better tillering ability and hybrids (KRH-2, HRI126, PHB-71 and DRRH-2 across the locations and BPT 5204 at Rajendranagar) were found promising and recorded higher grain yield over HYVs and scented cultivars having with moderate tillering. SRI method reduced the seed rate by 80% and nursery area, water requirement by 29% and growth duration by 8 – 12 days; thereby enhancing the water productivity and per day productivity of rice cultivars. SRI also helps to produce more seed and faster seed multiplication and also quality seed for higher productivity. The water saving alone should be a strong justification for adopting SRI method wherever water is not abundant. There is a need for further enhancing the productivity of rice under the SRI method by identifying the suitable cultivars, modification of practices to suit local agro-climatic conditions which plays an important role in mitigating the effects of climatic change.